PERADILAN PEREMPUAN: KEBIJAKAN KRIMINAL TERINTEGRASI DALAM MELINDUNGI PEREMPUAN (LP2M IAIN Jember (now UIN Kiai Haji Achmad Siddiq Jember), 2013)
The number of domestic violence cases increasing each year, as reflected in the Annual Report of the National Commission for Women, 2010. However, the actual number is not represent the reality. The people tend to be reluctant to report their cases because fear for bear the shame, stigmatization from society,